Endometrioid adenocarcinoma arising from adenomyosis: two case reports and a literature review - Yang, Jiaying; Wang, Qiuying; Han, Xiuchen; Liu, Qian (Frontiers in Surgery, 2023)
Background: Endometrioid adenocarcinoma is usually diagnosed by endometrial curettage with positive rate of 94%, while hysteroscopic examination can increase the positive rate. Differently, endometrioid adenocarcinoma arising from adenomyosis (EAAFA) is always misdiagnosed by endometrial curettage or hysteroscopy. EAAFA is rarely reported. Case description: We reported two cases of EAAFA with long-term follow-up for 9-10 years. The two cases were misdiagnosed even if endometrial curettage or hysteroscopy was performed. One case complained of postmenopausal vaginal bleeding with elevated CA199, she was diagnosed by fast frozen pathology during hysterectomy, then bilateral salpingo-oophorectomy and pelvic lymphadenectomy were performed. Another case, a premenopausal woman with acquired progressive dysmenorrhea was diagnosed as EAAFA by histopathological result after transvaginal hysterectomy and had to undergo reoperation. FIGO stage was ⅠB in both cases. Chemotherapy or radiotherapy was performed after operation. Patients were followed up for 9-10 years with no metastasis or recurrence observed. Conclusion: The diagnosis of EAAFA is always delayed because of tumor-free in eutopic endometrium and negative result of endometrial curettage or hysteroscopy examination. Fast frozen pathology of the whole uterus helps to diagnose EAAFA definitely and avoid reoperation. Adenocarcinoma foci of EAAFA usually involves the myometrium deeply. A better prognosis of EAAFA should be expected due to well-differentiation and negative lymphovascular space invasion.